Standalone Balloon Dilation versus Sinus Surgery for Chronic Rhinosinusitis: A Prospective, Multicenter, Randomized, Controlled Trial. Issue 5 (September 2013) - Cutler, Jeffrey; Bikhazi, Nadim; Light, Joshua; Truitt, Theodore; Schwartz, Michael; ,
Background: A prospective randomized controlled study was conducted on patients with chronic rhinosinusitis (CRS) to test the hypotheses that symptom improvement after balloon dilation was noninferior to functional endoscopic sinus surgery (FESS) and balloon dilation was superior to FESS for postoperative debridements. Methods: Adults with uncomplicated CRS of the maxillary sinuses with or without anterior ethmoid disease who met criteria for medically necessary FESS were randomized 1:1 to office balloon dilation or FESS and followed for 6 months. A minimum of 36 patients per arm were required to test the hypotheses with 90% power. Symptom improvement using the validated 20-item Sino-Nasal Outcome Test (SNOT-20) survey, debridements, recovery outcomes, complications, and revision surgeries were compared between groups. Results: Ninety-two patients (50 balloon dilation; 42 FESS) were treated. Mean SNOT-20 improvement was 1.67 ± 1.10 and 1.60 ± 0.96 in the balloon and FESS arms, respectively. Both groups showed clinically meaningful and statistically significant (p < 0.0001) improvement and the balloon arm was noninferior (p < 0.001) to FESS. The mean number of postprocedure debridements per patient was 0.1 ± 0.6 in the balloon arm versus 1.2 ± 1.0 in the FESS arm, with the balloon group showing superiority (p < 0.0001). Occurrence of postoperative nasal bleeding (p = 0.011), duration of prescription pain medication use (p < 0.001), recovery time (p = 0.002), and short-term symptom improvement (p = 0.014) were all significantly better for balloon dilation versus FESS. No complications occurred in either group and one revision surgery was reported in each arm. Conclusion: Balloon dilation is noninferior to FESS for symptom improvement and superior to FESS for postoperative debridements in patients with maxillary and anterior ethmoid disease. Balloon dilation is an effective treatment in patients with uncomplicated CRS who meet the criteria for medically necessary FESS.